Prediction of Restrained Shrinkage of New-to-old Concrete Interface - Wang, Huili; An, Dequan; Nie, Feng; Zhao, Hangshuai; Xu, Chunli (Periodica Polytechnica Civil Engineering, 2024)
The focus of this study is on the shrinkage differences between new and old concrete, which can cause cracks at the bonding surface of the interface. The effects of various factors on shrinkage, such as the content of shrinkage reducing admixtures (SRA) the content of basalt fibers (BF) and the roughness at the new-to-old concrete interface (RI) are also examined. In this research, nine groups old-new concrete composite specimens were tested for shrinkage to gather experimental data. The restrained shrinkage mechanical model (RSMM) was deduced, and the restrained shrinkage model based on grey correlation analysis (RMGC) was proposed. The effectiveness and convenience of both prediction methods were evaluated by comparing their results to the experimental data. It was determined that the RMGC was more effective and convenient. Additionally, the research found that as the content of SRA and BF increases, shrinkage decreases. The effect of SRA was found to be more significant. As RI increases, shrinkage undergoes an initial increase and then decreases. The study can be used to inform the design and construction of structures that use both new and old concrete.